Wound infections secondary to snakebite - Atul Garg; S. Sujatha; Jaya Garg; N. Srinivas Acharya; Subhash Chandra Parija (Journal of Infection in Developing Countries)
Background: The study was performed to identify the important bacterial pathogens responsible for wound infections secondary to snakebite and to determine their antimicrobial susceptibility. Methodology: All cases of wound infection secondary to snakebite were included in this retrospective study. Infected tissues were surgically debrided and inoculated on blood agar and MacConkey agar for aerobic bacterial culture, followed by antimicrobial susceptibility testing of the isolates by Kirby-Bauer disk diffusion method. Results: Staphylococcus aureus (32%) was the most common isolate followed by Escherichia coli (15%); monomicrobial infections were more frequent than polymicrobial infections. The majority of the isolates were antibiotic sensitive. Ciprofloxacin, an oral drug covering both Gram-positive and Gram-negative isolates, was the most frequently prescribed antibiotic. The patients responded well to the treatment. Conclusion: The results of this study will be helpful in deciding the empirical antibiotic therapy in cases of wound infection secondary to snakebite in regions of Southeast Asia.